Vacuum heat insulation material and HIPE foam
The use of a HIPE form composed of a crosslinked styrene monomer polymer as the core material addresses the mass and productivity issues of inorganic fibers and foam-based materials, resulting in lightweight, high-insulation vacuum insulation materials with enhanced manufacturing efficiency and thermal performance.
Patent Information
- Application Number
- JP2023118284
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-20
- Publication Date
- 2025-01-30
AI Technical Summary
Existing vacuum insulation materials using inorganic fibers as core materials face challenges with high mass and low productivity, while foam-based core materials have limitations in insulation performance and manufacturing efficiency.
A vacuum insulation material using a HIPE form composed of a crosslinked polymer of styrene monomer as the core material, with specific density, strut width, and compression stress characteristics, enhancing thermal insulation and manufacturing efficiency.
The HIPE form provides lightweight, high-insulation vacuum insulation materials with improved manufacturing properties and reduced contraction under pressure differences, achieving thermal conductivity below 7.5 MW/(m·K) and maintaining structural integrity.
Smart Images

Figure 2025015122000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to vacuum insulation materials and HIPE foams. [Background technology]
[0002] In recent years, efforts to reduce greenhouse gas emissions have been promoted to prevent global warming. From this perspective, the use of vacuum insulation materials has been promoted to reduce energy consumption in electrical appliances, vehicles, equipment, buildings, etc. Vacuum insulation materials have an outer packaging material and a core material enclosed within the outer packaging material. The internal space of the vacuum insulation material is decompressed, and high insulation properties are achieved by suppressing heat transfer due to convection, etc.
[0003] Conventionally, inorganic fibers with low thermal conductivity, such as glass wool, have been used as the core material for vacuum insulation materials. However, when inorganic fibers are used as the core material, it is necessary to encapsulate a relatively large amount of inorganic fibers in the outer packaging material, taking into consideration the shrinkage that occurs when the internal space is decompressed. Therefore, there is a problem that vacuum insulation materials having a core material made of inorganic fibers tend to be large in mass.
[0004] In order to solve this problem, the use of a resin foam, which is lighter than inorganic fibers, as the core material of the vacuum insulation material has been considered. For example, Patent Document 1 describes the use of an open-cell microcellular alkenyl aromatic polymer foam as the core material of the vacuum insulation material. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Special Publication No. 11-504362 Summary of the Invention [Problem to be solved by the invention]
[0006] However, in Patent Document 1, there was room for improvement in order to further improve the heat insulating properties of the vacuum insulation material when the foam is used as the core material of the vacuum insulation material. Also, when the foam of Patent Document 1 is used as the core material of the vacuum insulation material, it takes a relatively long time to reduce the pressure in the internal space of the vacuum insulation material, which causes a problem of low productivity.
[0007] The present invention has been made in consideration of the above background, and aims to provide a vacuum insulation material that is easy to manufacture, lightweight, and has good thermal insulation properties, and a HIPE foam that is suitable as the core material of this vacuum insulation material. [Means for solving the problem]
[0008] One aspect of the present invention is a vacuum insulation material according to the following items (1) to (5).
[0009] [1] A vacuum insulation material having an outer packaging material and a core material enclosed in the outer packaging material, The core material is made of HIPE foam, The HIPE foam is composed of a cross-linked polymer of a styrene-based monomer, The apparent density of the HIPE foam is 25 kg / m 3 More than 90kg / m 3 is as follows: The average strut width of the HIPE foam is 2 μm or more and 10 μm or less, A vacuum insulation material, wherein the HIPE foam has a compressive stress at 5% strain of 105 kPa or more.
[0010] [2] The vacuum insulation material according to [1], wherein the thermal conductivity of the vacuum insulation material is less than 7.5 mW / (m·K). [3] The vacuum insulation material according to [1] or [2], wherein the thickness of the HIPE foam is 2 mm or more and 30 mm or less. [4] The vacuum insulation material according to any one of [1] to [3], wherein the HIPE foam has a glass transition temperature of 70°C or higher and 150°C or lower. [5] The molecular weight between crosslinking points of the HIPE foam is 8×10 3 More than 2×105 The vacuum insulation material according to any one of [1] to [4] below.
[0011] Another aspect of the present invention is a HIPE foam according to the following items [6] to [9].
[0012] [6] A HIPE foam used as a core material in a vacuum insulation material having an outer packaging material and a core material enclosed in the outer packaging material, The HIPE foam is composed of a cross-linked polymer of a styrene-based monomer, The apparent density of the HIPE foam is 25 kg / m 3 More than 90kg / m 3 is as follows: The average strut width of the HIPE foam is 2 μm or more and 10 μm or less, The HIPE foam has a compressive stress at 5% strain of 105 kPa or more.
[0013] [7] The HIPE foam described in [6], wherein the thickness of the HIPE foam is 2 mm or more and 30 mm or less. [8] The HIPE foam according to [6] or [7], wherein the glass transition temperature of the HIPE foam is 70°C or higher and 150°C or lower. [9] The molecular weight between crosslinking points of the HIPE foam is 8×10 3 More than 2×10 5 A HIPE form according to any one of [6] to [8] below. Effect of the Invention
[0014] According to the above-mentioned embodiment, it is possible to provide a vacuum insulation material which is easy to manufacture, lightweight and has good thermal insulation properties, and a HIPE foam suitable for use as the core material of this vacuum insulation material. [Brief description of the drawings]
[0015] [Figure 1] FIG. 1 is a partial cross-sectional view showing a main part of a vacuum insulation material. [Diagram 2]FIG. 2 is an explanatory diagram showing an enlarged photograph of a cross section of the HIPE foam constituting the core material. [Diagram 3] FIG. 3 is an explanatory diagram showing an example of a temperature-storage modulus curve showing the relationship between the temperature T and the storage modulus E′ of a HIPE foam. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] (Vacuum insulation material) As shown in Fig. 1, the vacuum insulation material 1 has an outer packaging material 11 and a core material 12 enclosed within the outer packaging material 11. The core material 12 is composed of a HIPE foam 2 having an apparent density, average strut width, and compressive stress at 5% strain within the above-mentioned specific ranges. The HIPE foam 2 is also composed of a cross-linked polymer of a styrene-based monomer. The configuration of each part of the vacuum insulation material 1 will be described in detail below.
[0017] [HIPE Form] The core material of the vacuum insulation material is a HIPE foam composed of a crosslinked polymer of a styrene-based monomer. The HIPE foam is a porous polymer also called polyHIPE foam, polyHIPE material, HIPE-derived foam material, high internal phase emulsion porous body, high internal phase emulsion foam body, etc. The HIPE foam is obtained, for example, by polymerizing a monomer in a water-in-oil type high internal phase emulsion (i.e., HIPE) in which a high ratio of aqueous phase is contained in an organic phase. The HIPE foam obtained in this way has an open-cell structure in which a large number of bubbles exist in the structure and a large number of through holes are formed in the bubble walls existing between adjacent bubbles. Since the HIPE foam has an open-cell structure, the gas inside the HIPE foam is easily exhausted to the outside. Therefore, when the HIPE foam is used as the core material of the vacuum insulation material, the time required for the depressurization process can be shortened.
[0018] HIPE foams are obtained, for example, by polymerizing styrene-based monomers in the presence of a crosslinking agent in a water-in-oil type high internal phase emulsion in which a high ratio of the aqueous phase is encapsulated in the organic phase. HIPE foams are composed of crosslinked polymers containing monomer components derived from styrene-based monomers. More specifically, HIPE foams contain monomer components derived from styrene-based monomers in the polymer backbone of the crosslinked polymer.
[0019] In addition, HIPE foam is a porous cured material obtained by curing a high internal phase emulsion, and the cell walls can be said to be composed of the crosslinked polymer (e.g., styrene-based polymer). The cells can also be said to be pores. The shape of the cell walls and cells in HIPE foam reflects the dispersion form of the organic phase and the aqueous phase in the high internal phase emulsion and the dispersion form of the aqueous phase (i.e., the dispersed phase) during polymerization.
[0020] In the manufacturing process of HIPE foam, the crosslinked polymer is difficult to stretch. Therefore, HIPE foam generally has a porous body in which the crosslinked polymer is difficult to be oriented and the shape of the bubbles is less anisotropic. HIPE foam can be easily distinguished from foams that are stretched during manufacturing, such as foams obtained by extrusion foaming using an extruder, and foamed bead moldings obtained by foaming expandable resin beads and molding the foamed beads in a mold.
[0021] In addition, since HIPE foam does not require the use of volatile components such as foaming agents in its manufacturing process, the amount of volatile components emitted from the HIPE foam can be easily reduced even when no operation is performed to remove volatile components from the crosslinked polymer. Furthermore, since the HIPE foam has the open cell structure described above, the gas present in the bubbles of the HIPE foam can easily move to the outside of the HIPE foam. Therefore, by using the HIPE foam as the core material of the vacuum insulation material, the gas present in the internal space can be quickly exhausted during the manufacturing process of the vacuum insulation material. As a result, the manufacturability of the vacuum insulation material can be easily improved.
[0022] [Apparent density of HIPE foam] The apparent density of the HIPE foam is 25 kg / m 3 More than 90kg / m 3 The apparent density of the HIPE foam is set within the above-mentioned specific range, thereby ensuring the strength of the HIPE foam while improving its light weight. By using such a HIPE foam as a core material of a vacuum insulation material, the heat insulating property of the vacuum insulation material can be improved. Furthermore, in this case, the mass of the vacuum insulation material can be easily reduced, and the shape of the core material can be maintained even when the vacuum insulation material is enclosed inside the outer packaging material and a pressure difference is applied between the inside and outside of the outer packaging material.
[0023] If the apparent density of the HIPE foam is too low, the heat insulating property of the vacuum insulation material using the HIPE foam as the core material is likely to be insufficient. In addition, the strength of the HIPE foam is insufficient, and when the internal space is decompressed during the manufacturing process of the vacuum insulation material, the core material is likely to shrink due to the pressure difference between the atmospheric pressure and the pressure of the internal space. In this case, the dimensions of the vacuum insulation material may be easily deviated from the desired dimensions. In some cases, the air bubbles may be crushed, and it may not be possible to form a vacuum space inside the vacuum insulation material. In this way, a HIPE foam with a low apparent density may not be suitable for use as a core material of a vacuum insulation material. On the other hand, if the apparent density of the HIPE foam is too high, the heat insulating property of the vacuum insulation material using the HIPE foam as the core material is likely to be insufficient.
[0024] The apparent density of HIPE foam is 30kg / m 3 It is preferable that the saturation temperature is 35 kg / m or more. 3 More preferably, it is 40 kg / m or more. 3 In this case, the strength of the HIPE foam can be further increased, and the shrinkage of the core material in the vacuum insulation material can be further suppressed.
[0025] The apparent density of HIPE foam is 80kg / m 3It is preferable that the thickness is less than 70 kg / m 3 More preferably, it is 65 kg / m or less. 3 More preferably, it is 60 kg / m or less. 3 It is particularly preferable that the HIPE foam is no greater than 100%. In this case, the weight of the HIPE foam can be reduced more easily.
[0026] In determining the preferred range of the apparent density of the HIPE foam, the upper and lower limits of the preferred range of the apparent density of the HIPE foam described above can be combined arbitrarily. For example, the preferred range of the apparent density of the HIPE foam is 30 kg / m 3 More than 80kg / m 3 It may be less than 30 kg / m 3 More than 70kg / m 3 may be less than 35 kg / m 3 More than 65kg / m 3 may be less than 35 kg / m 3 More than 60kg / m 3 It may be less than 40 kg / m 3 More than 60kg / m 3 It may be the following.
[0027] The apparent density of the HIPE foam described above is calculated by dividing the mass of the HIPE foam by the volume of the HIPE foam. The volume of the HIPE foam can be calculated based on the outer dimensions of the HIPE foam after it is removed from the outer packaging material.
[0028] The apparent density of the HIPE foam is adjusted to be within the above range by adjusting the ratio of the amount of the organic phase (specifically, the total amount of the styrene-based monomer, crosslinking agent, emulsifier, and polymerization initiator) to the amount of the aqueous phase (specifically, the amount of the aqueous liquid) in the HIPE foam manufacturing method described below.
[0029] [HIPE foam cell structure] The HIPE foam is a porous polymer having an open-cell structure as described above. As illustrated in FIG. 2, the HIPE foam 2 has a cell wall 21 made of a crosslinked polymer. The HIPE foam 2 has a cell structure in which many cells 22 are uniformly present, and has an open-cell structure in which many through-holes 23 are formed through the cell wall 21 and communicate between adjacent cells. In FIG. 2, the cells 22 are the parts surrounded by the cell wall 21. The through-holes 23 are holes that penetrate the cell wall 21 and communicate between adjacent cells 22. Specifically, the through-holes 23 are formed in the cell wall 21 and communicate between adjacent cells 22 across the cell wall 21. The through-holes 23 can also be called through windows or connecting holes.
[0030] The cell walls 21 have columnar struts 211 that separate adjacent through holes 23, and hubs 212 where the struts 211 join together. The average strut width of the HIPE foam is 2 μm or more and 10 μm or less. By setting the apparent density of the HIPE foam within the above-mentioned specific range and further setting the average strut width within the above-mentioned specific range, the thermal insulation properties of the vacuum insulation material can be improved.
[0031] The thermal conductivity of the vacuum insulation material can be improved by setting the average strut width of the HIPE foam within the above-mentioned specific range for the following reasons, for example. The internal space of the vacuum insulation material has a pressure lower than atmospheric pressure, so heat conduction by gas remaining in the internal space is suppressed. In addition, the HIPE foam has a fine bubble structure of about tens to hundreds of μm, so heat conduction by convection is suppressed. Therefore, it is considered that the form of heat transfer inside the vacuum insulation material is mainly two-way: heat conduction via the bubble walls 21 of the HIPE foam and heat radiation from the bubble walls 21.
[0032] In order to suppress heat transfer by conduction, it is necessary to increase the thermal resistance of the object through which the heat is transferred. The smaller the cross-sectional area of the object, the higher the thermal resistance of the object. Therefore, by making the struts of the HIPE foam thinner, it is thought that it is possible to increase the thermal resistance of the struts and suppress heat transfer by conduction. It is also thought that lowering the apparent density of the HIPE foam and increasing the void ratio in the vacuum insulation material is also effective in suppressing heat transfer by conduction. In this way, it is thought that heat conduction can be suppressed by lowering the apparent density of the HIPE foam.
[0033] On the other hand, in order to suppress heat transfer due to thermal radiation, it is sufficient to block the electromagnetic waves (specifically, infrared rays) emitted from an object with a shield. Therefore, for example, by making the struts of the HIPE foam thicker, it is thought that the struts will be able to block the electromagnetic waves more easily, and heat transfer due to thermal radiation will be suppressed. In addition, in order to suppress heat transfer due to thermal radiation, it is also thought that increasing the apparent density of the HIPE foam and the volume fraction of the cell walls will be effective. In this way, by increasing the resin fraction of the cell walls in the HIPE foam, it is thought that electromagnetic waves will be more easily blocked, and heat radiation will be suppressed.
[0034] As described above, in the core material made of HIPE foam, when the struts are made thinner, the thermal resistance of the struts increases, and heat transfer by thermal conduction can be suppressed. On the other hand, when the struts are made thinner, it is considered that electromagnetic waves are less likely to hit the struts, and it becomes difficult to suppress heat transfer by thermal radiation. Also, when the struts are made thicker, electromagnetic waves are more likely to hit the struts, and it becomes possible to suppress heat transfer by thermal radiation. On the other hand, when the struts are made thicker, it is considered that the thermal resistance of the struts decreases, and it becomes difficult to suppress heat transfer by thermal conduction. Similarly, when the apparent density of the HIPE foam is reduced, heat conduction can be suppressed, but heat radiation increases. Also, when the apparent density of the HIPE foam is increased, heat radiation can be suppressed, but heat conduction increases. Therefore, it is considered that by setting the average strut width and apparent density of the HIPE foam within the above-mentioned specific range, both heat transfer by thermal conduction and heat transfer by thermal radiation can be suppressed in a balanced manner, and the thermal insulation of the vacuum insulation material can be improved.
[0035] The method for measuring the average strut width in HIPE foam is as follows. First, the HIPE foam is cut at an arbitrary cross section to expose the cut surface. Next, the cut surface is observed using a scanning electron microscope or the like to obtain an enlarged photograph of the cut surface. On this enlarged photograph, multiple struts are randomly selected, and the width of the narrowest part of each strut is measured. The arithmetic mean value of the strut widths thus obtained is taken as the average strut width. The number of struts used to calculate the average strut width is not particularly limited, but the more struts there are, the more accurate the average strut width can be calculated. From this viewpoint, it is preferable that the number of struts used to calculate the average strut width is, for example, 20 or more.
[0036] The average strut width of the HIPE foam can be controlled by adjusting the droplet size of the aqueous phase (i.e., the dispersed phase) of the high internal phase emulsion and the ratio of the amount of the organic phase to the amount of the aqueous phase in the manufacturing method of the HIPE foam described below. For example, the average strut width of the HIPE foam can be narrowed by reducing the amount of the organic phase. Also, even if the amount of the organic phase is the same, increasing the power during stirring reduces the droplet size of the aqueous phase, and the average strut width of the HIPE foam can be narrowed.
[0037] [Average bubble diameter of HIPE foam] The average cell diameter of the HIPE foam is preferably 10 μm or more and 100 μm or less, more preferably 15 μm or more and 90 μm or less, and even more preferably 20 μm or more and 80 μm or less. By setting the average cell diameter of the HIPE foam within the above-mentioned specific range, the average strut width of the HIPE foam can be more easily adjusted to within the above-mentioned specific range.
[0038] The average bubble diameter of the HIPE foam is specifically the average value of the circle-equivalent diameter of the bubbles. The circle-equivalent diameter of the bubbles is the diameter of a circle having the same area as the area of the bubbles in the cross section of the HIPE foam. The average bubble diameter of the HIPE foam can be obtained, for example, by image analysis of the open-cell structure of the HIPE foam. A more detailed method for measuring the average bubble diameter will be described in the Examples.
[0039] [HIPE foam compression properties] The HIPE foam has a compressive stress σ5 at 5% strain of 105 kPa or more. A HIPE foam having a compressive stress σ5 at 5% strain within the above-mentioned specific range has sufficient strength, so that it is sealed inside an outer packaging material and is unlikely to shrink even when a pressure difference is applied between the inside and outside of the outer packaging material. Therefore, by using such a HIPE foam as the core material of a vacuum insulation material, a vacuum-state internal space can be formed inside the outer packaging material, improving the insulation properties of the vacuum insulation material.
[0040] If the compressive stress σ5 at 5% strain of the HIPE foam is too low, the core material will be prone to shrinkage due to the pressure difference between atmospheric pressure and the pressure in the internal space when the internal space is reduced in pressure during the manufacturing process of the vacuum insulation material, and the HIPE foam may not be suitable for use as a core material for vacuum insulation material.
[0041] From the viewpoint of increasing the strength of the HIPE foam and suppressing the shrinkage of the core material, the compressive stress σ5 at 5% strain of the HIPE foam is preferably 120 kPa or more, more preferably 140 kPa or more, and particularly preferably 160 kPa or more. From the viewpoint of suppressing the shrinkage of the core material, the upper limit of the compressive stress σ5 at 5% strain of the HIPE foam is not particularly limited, but the upper limit of the compressive stress σ5 at 5% strain of the HIPE foam made of a crosslinked polymer of a styrene-based monomer is usually about 900 kPa.
[0042] In addition, the compressive stress σ of HIPE foam at 50% strain 50 Ratio of compressive stress σ5 at 5% strain to σ5 / σ 50 is preferably greater than 0.5. The compressive stress at 5% strain σ5 and the compressive stress at 50% strain σ 50 is a value obtained by measurement based on JIS K6767:1999.
[0043] [Crosslinked polymer] HIPE foam is composed of a crosslinked polymer of a styrene-based monomer. That is, the resin portion of the HIPE foam is a polymer obtained by polymerizing a styrene-based monomer in the presence of a crosslinking agent, and contains a monomer component derived from the styrene-based monomer and a component derived from the crosslinking agent. The proportion of the styrene-based monomer in 100% by mass of the monomer components constituting the crosslinked polymer is preferably 70% by mass or more, more preferably 80% by mass or more, and even more preferably 90% by mass or more.
[0044] Examples of styrene-based monomers include styrene compounds having one vinyl group on an aromatic ring, such as styrene, α-methylstyrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, p-ethylstyrene, 2,4-dimethylstyrene, p-methoxystyrene, pn-butylstyrene, pt-butylstyrene, o-chlorostyrene, m-chlorostyrene, p-chlorostyrene, 2,4,6-tribromostyrene, styrenesulfonic acid, and sodium styrenesulfonate.
[0045] As the styrene-based monomer, it is preferable to use styrene. When styrene is used as the styrene-based monomer, the content of styrene in the styrene-based monomer is preferably 50% by mass or more, more preferably 80% by mass or more, and further preferably 90% by mass or more.
[0046] The resin portion of the HIPE foam may contain a monomer component derived from an acrylic monomer within a range that does not impair the above-mentioned action and effect. In other words, the resin portion of the HIPE foam may be a crosslinked copolymer obtained by polymerizing a styrene monomer and an acrylic monomer in the presence of a crosslinking agent. Examples of the acrylic monomer include alkyl acrylates such as methyl acrylate, ethyl acrylate, butyl acrylate, 2-ethylhexyl acrylate, hydroxyethyl acrylate, cyclohexyl acrylate, phenyl acrylate, benzyl acrylate, isobornyl acrylate, dicyclopentanyl acrylate, and adamantyl acrylate; and alkyl methacrylates such as methyl methacrylate, ethyl methacrylate, propyl methacrylate, butyl methacrylate, 2-ethylhexyl methacrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, cyclohexyl methacrylate, phenyl methacrylate, benzyl methacrylate, isobornyl methacrylate, dicyclopentanyl methacrylate, and adamantyl methacrylate. Examples of the acrylic monomer include (meth)acrylic esters having one vinyl group per molecule. In addition, among the monomer components constituting the crosslinked polymer, the proportion of the acrylic monomer component is preferably 30 mass% or less, more preferably 20 mass% or less, and even more preferably 10 mass% or less, relative to 100 mass% in total of the styrene monomer component and the acrylic monomer component.
[0047] A crosslinking agent is a compound that crosslinks (bonds) between polymer chains that constitute a polymer to form a crosslinked structure in the polymer. More specifically, as the crosslinking agent, for example, a vinyl-based compound having at least two crosslinkable functional groups selected from a vinyl group and an isopropenyl group in the molecule is used. When the crosslinked polymer contains a crosslinking agent component, the rigidity and toughness of the crosslinked polymer can be increased. The vinyl-based compound also includes a compound containing a vinyl group and / or an isopropenyl group in the structure of the crosslinkable functional group, such as an acryloyl group or a methacryloyl group. From the viewpoint of stably polymerizing the crosslinking agent, the number of crosslinkable functional groups contained in the crosslinking agent is preferably 6 or less, more preferably 5 or less, and more preferably 4 or less per molecule of the crosslinking agent. In addition, from the viewpoint of making it easier to increase the toughness of the crosslinked polymer, the crosslinking agent preferably has crosslinkable functional groups at least at both ends of the molecule, and more preferably has crosslinkable functional groups only at both ends of the molecule.
[0048] Examples of the crosslinking agent include vinyl compounds having two or more crosslinkable functional groups per molecule, such as divinylbenzene, triallyl isocyanurate, esters of polyhydric alcohols and (meth)acrylic acid, esters of polyether glycols and (meth)acrylic acid, esters of urethane oligomers and (meth)acrylic acid, esters of epoxy oligomers and (meth)acrylic acid, and (meth)acrylic-modified silicones. Examples of the esters of polyhydric alcohols and (meth)acrylic acid include butanediol (meth)acrylates such as butanediol diacrylate; hexanediol (meth)acrylates such as hexanediol diacrylate; nonanediol (meth)acrylates such as nonanediol diacrylate; decanediol (meth)acrylates such as decanediol diacrylate; trimethylolpropane (meth)acrylates such as trimethylolpropane triacrylate; and pentaerythritol (meth)acrylates such as pentaerythritol tetraacrylate. Examples of the ester of polyether glycol and (meth)acrylic acid include polyethylene glycol (meth)acrylates such as polyethylene glycol diacrylate; polypropylene (meth)acrylates such as polypropylene glycol diacrylate; and polytetramethylene glycol (meth)acrylates such as polytetramethylene glycol diacrylate. The crosslinkable functional group in the crosslinking agent is preferably a vinyl group and / or an isopropenyl group. These crosslinking agents may be used alone, or two or more crosslinking agents may be used in combination. In other words, the crosslinking agent component contained in the HIPE foam may be one type, or two or more types.
[0049] From the viewpoint of increasing the strength of the HIPE foam and making it easier to maintain the shape of the core material even when it is enclosed in an outer packaging material, the main component of the crosslinking agent is preferably a vinyl-based compound having a molecular weight of 100 to 400, and more preferably a vinyl-based compound having a molecular weight of 100 to 250. The main component of the crosslinking agent means a component that accounts for 50% by mass or more of the crosslinking agent. The proportion of the vinyl-based compound that is the main component of the crosslinking agent is preferably 80% by mass or more, more preferably 90% by mass or more, even more preferably 95% by mass or more, and particularly preferably 98% by mass or more.
[0050] The content of the styrene monomer component in the HIPE foam, i.e., the monomer component derived from a styrene monomer, is preferably 80 parts by mass or more and 97 parts by mass or less, and more preferably 85 parts by mass or more and 95 parts by mass or less, relative to 100 parts by mass of the total of the styrene monomer component and the crosslinking agent component. In this case, the strength of the HIPE foam can be more easily increased to a range suitable for use as a core material for a vacuum insulation material.
[0051] [HIPE foam shape] The shape of the HIPE foam is not particularly limited, but from the viewpoint of improving the heat insulating property and handling property of the vacuum insulation material, the HIPE foam is preferably in a plate shape. From the same viewpoint, the thickness of the HIPE foam is preferably 2 mm or more and 30 mm or less.
[0052] [Thermal conductivity of HIPE foam] The thermal conductivity of the HIPE foam is preferably 40 mW / (m·K) or less. By using a HIPE foam having a thermal conductivity within the above-mentioned specific range as the core material of the vacuum insulation material, the thermal insulation properties of the vacuum insulation material can be further improved. From the viewpoint of improving the thermal insulation properties of the vacuum insulation material, the lower limit of the thermal conductivity of the HIPE foam is not particularly limited, but the lower limit of the thermal conductivity of the HIPE foam is about 20 mW / (m·K) due to its configuration.
[0053] The thermal conductivity of the HIPE foam can be measured by the heat flow meter method specified in JIS A1412-2:1999. More specifically, the thermal conductivity of the HIPE foam can be measured using, for example, a thermal conductivity measuring device ("HC-074 / 200" manufactured by Eiko Seiki Co., Ltd.). In measuring the thermal conductivity, first, a flat plate-shaped test specimen with a length of 180 mm, a width of 180 mm, and a thickness of 10 mm is prepared from the HIPE foam. Of the two faces of this test specimen surrounded by the side with a length of 180 mm and the side with a width of 180 mm, one face is brought into contact with the high-temperature face, and the other face is brought into contact with the low-temperature face. In this state, a temperature difference is given between the high-temperature face and the low-temperature face. Then, the heat flow passing through the test specimen in a steady state is measured, and the thermal conductivity can be calculated based on the obtained heat flow, etc. When measuring the thermal conductivity, the temperature of the high-temperature face should be 33°C, the temperature of the low-temperature face should be 13°C, and the average temperature of the test specimen should be 23°C.
[0054] [Glass transition temperature of HIPE foam] The glass transition temperature Tg of the HIPE foam is preferably from 70° C. to 150° C., more preferably from 80° C. to 140° C., and even more preferably from 90° C. to 130° C. In this case, the strength of the HIPE foam can be more easily increased to a range suitable for use as a core material for a vacuum insulation material.
[0055] The glass transition temperature Tg of the HIPE foam is measured based on JIS K7121:1987. Specifically, a test piece made of HIPE foam is prepared, and the condition of the test piece is adjusted based on "(3) Measurement of glass transition temperature after a certain heat treatment" in "3. Conditioning of test piece" in JIS K7121:1987. Then, a differential scanning calorimetry (DSC) is performed on the resin constituting the conditioned test piece to obtain a DSC curve. The midpoint glass transition temperature in the DSC curve obtained in this way is taken as the glass transition temperature Tg of the HIPE foam.
[0056] The glass transition temperature Tg of the HIPE foam is adjusted to fall within the above range by adjusting the type and mixing ratio of the styrene monomer, the type and mixing ratio of the crosslinking agent, etc. in the production method of the HIPE foam described below.
[0057] [Molecular weight between crosslink points of HIPE foam] The molecular weight between crosslink points of the HIPE foam, Mc, is 8×10 3 More than 2×10 5 It is preferable that the value is less than 1×10 4 More than 1×10 5 More preferably, it is 2×10 4 8×10 or more 4 In this case, the strength of the HIPE foam can be more easily increased to a range suitable for use as the core material of a vacuum insulation material.
[0058] The molecular weight Mc between crosslinks of the HIPE foam is measured as follows. Dynamic viscoelasticity measurement is performed on the HIPE foam under the following measurement conditions: frequency: 1 Hz, load: 98 mN, deformation mode: compression. During the heating process of the dynamic viscoelasticity measurement, the temperature-storage modulus curve (hereinafter referred to as the "T-E' curve") obtained by plotting temperature on the horizontal axis and storage modulus E' on the vertical axis shows a relatively flat shape until the temperature of the HIPE foam exceeds the glass transition temperature Tg. When the temperature of the HIPE foam rises to the vicinity of the glass transition temperature Tg, the crosslinked polymer constituting the HIPE foam transitions from a glassy state to a rubbery state. Then, when the crosslinked polymer transitions from a glassy state to a rubbery state, the storage modulus E' in the T-E' curve drops sharply (see Figure 3).
[0059] After the temperature of the HIPE foam exceeds the glass transition temperature Tg, the T-E' curve again shows a relatively flat shape. The flat portion of the T-E' curve after exceeding the glass transition temperature Tg is called the plateau region (rubber-like plateau). In the plateau region, E' is proportional to temperature, so the molecular weight Mc between crosslinks can be calculated from the following formula (I). Mc = 2(1 + μ)ρRT / E' (I)
[0060] In the above formula (I), μ is the Poisson's ratio, and ρ is the apparent density of the HIPE foam (unit: kg / m 3 ), R is the gas constant, T is the temperature (unit: K) at any point on the rubbery flat, and E' is the storage modulus (unit: kPa) at that temperature T. The value of Poisson's ratio μ is specifically 0.5, and the value of the gas constant R is specifically 8.314 J / (K mol).
[0061] From the viewpoint of appropriately calculating the molecular weight Mc between crosslinking points, it is preferable that the temperature T used for calculating the molecular weight Mc between crosslinking points is selected from the range of Tg+50°C to Tg+80°C (where Tg is the glass transition temperature of the HIPE foam).
[0062] The Poisson's ratio is a value specific to a material, and is calculated by dividing the strain that occurs in the direction perpendicular to the stress when stress is applied to an object by the strain that occurs in the direction parallel to the stress, and multiplying this value by -1. Theoretically, the Poisson's ratio ranges from -1 to 0.5. If the Poisson's ratio is a negative value, it means that when the HIPE foam is crushed in the vertical direction, it is also crushed in the horizontal direction. Conversely, if the Poisson's ratio is a positive value, it means that when the HIPE foam is crushed in the vertical direction, it stretches in the horizontal direction. Under the measurement conditions of the dynamic viscoelasticity measurement described above, the strain generated in the crosslinked polymer that constitutes the HIPE foam is very small and can be considered to have no volume change, so the storage modulus E' and the molecular weight between crosslinking points Mc are calculated under the condition of constant volume, i.e., a Poisson's ratio of 0.5.
[0063] The molecular weight Mc between crosslinking points of the HIPE foam can be reduced by adding a crosslinking agent in the manufacturing method of the HIPE foam described below, and can be adjusted to a desired value by adjusting the type and mixing ratio of the crosslinking agent, the type and mixing ratio of the monomer, etc. For example, the molecular weight between crosslinking points can be reduced by including a large amount of the crosslinking agent component in the crosslinked polymer.
[0064] [Outer packaging material] The packaging material of the vacuum insulation material has low water vapor permeability and gas permeability, i.e., gas barrier properties. This makes it possible to maintain the pressure in the internal space of the vacuum insulation material lower than atmospheric pressure and maintain the heat insulating properties of the vacuum insulation material. As the packaging material, for example, a multilayer film having a gas barrier layer made of a material having gas barrier properties and a heat-sealed layer laminated on one side of the gas barrier layer is used.
[0065] The gas barrier layer may be made of a metal foil or a metal-deposited thin film made of a metal such as aluminum. The thermal adhesion layer may be made of a polyolefin resin film such as polyethylene or polypropylene, a polyester resin film such as polyethylene terephthalate or polybutylene terephthalate, or a polyvinyl chloride resin film such as polyvinylidene chloride.
[0066] The outer packaging material preferably further has a protective film layer laminated on the back side of the surface of the gas barrier layer having the heat-sealing layer. Examples of materials constituting the protective film layer include polyamide resin films such as nylon; polyester resin films such as polyethylene terephthalate and polybutylene terephthalate. The number of the protective film layers may be one or more. For example, the outer packaging material may have one protective film layer on the back side of the surface of the gas barrier layer having the heat-sealing layer laminated thereon, or may have two or more protective film layers laminated together. The thickness of the outer packaging material is preferably 30 μm or more and 300 μm or less.
[0067] [Thermal conductivity of vacuum insulation material] The thermal conductivity of the vacuum insulation material is preferably less than 7.5 mW / (m·K). In this case, the thermal insulation property of the vacuum insulation material can be further improved. From the viewpoint of improving the thermal insulation property of the vacuum insulation material, the lower limit of the thermal conductivity of the vacuum insulation material is not particularly limited, but when the specific HIPE foam is used as the core material, the lower limit of the thermal conductivity of the vacuum insulation material is about 3.0 mW / (m·K).
[0068] The thermal conductivity of vacuum insulation material can be measured by the heat flow meter method specified in JIS A1412-2: 1999. The method for measuring the thermal conductivity of vacuum insulation material is the same as the method for measuring the thermal conductivity of HIPE foam described above, except that vacuum insulation material is used as the test specimen.
[0069] (Manufacturing method of vacuum insulation material) The method for producing the vacuum insulation material is not particularly limited, and known methods can be adopted. For example, the surface of the core material is wrapped with an outer packaging material, and then the gas present in the inner space of the vacuum insulation material is exhausted to make the inner space a vacuum state, and the core material is sealed with the outer packaging material while maintaining this vacuum state, thereby obtaining a vacuum insulation material. The degree of vacuum inside the vacuum insulation material is preferably 10 Pa or less, more preferably 5 Pa or less, from the viewpoint of obtaining better heat insulation.
[0070] A core material made of at least HIPE foam is enclosed in the internal space of the vacuum insulation material surrounded by the outer packaging material. In addition to the core material, an adsorbent that adsorbs moisture and / or gas may be enclosed in the internal space of the vacuum insulation material. In this case, the pressure in the internal space of the vacuum insulation material can be kept lower than atmospheric pressure for a longer period of time. As a result, the insulating properties of the vacuum insulation material can be maintained for a longer period of time.
[0071] (HIPE foam manufacturing method) HIPE foam, which is the core material of vacuum insulation materials, is obtained by polymerizing a water-in-oil type high internal phase emulsion. The organic phase of the water-in-oil type high internal phase emulsion is a continuous phase containing styrene monomers, crosslinking agents, emulsifiers, polymerization initiators, etc., and the aqueous phase is a dispersed phase containing water such as deionized water.
[0072] A method for producing a HIPE foam includes, for example, an emulsification step of forming a water-in-oil type high internal phase emulsion in which an aqueous phase containing water is encapsulated in an organic phase containing a styrene-based monomer, a crosslinking agent, an emulsifier, and a polymerization initiator, and a polymerization step of polymerizing the styrene-based monomer and the crosslinking agent in the water-in-oil type high internal phase emulsion filled in a reaction vessel.
[0073] [Emulsification process] In the emulsification step, an oily liquid (organic phase) containing organic substances such as a styrene monomer, a crosslinking agent, an emulsifier, and a polymerization initiator and an aqueous liquid (aqueous phase) containing water are mixed and emulsified to prepare a water-in-oil type high internal phase emulsion. In the emulsification step, a high internal phase emulsion can be prepared by mixing an oily liquid and an aqueous liquid so that the aqueous phase is, for example, three times or more of the organic phase in volume ratio. The ratio of the aqueous phase contained in the organic phase can be adjusted by the mass ratio of the organic phase to the aqueous phase. The content of the aqueous phase in the high internal phase emulsion is preferably 250 parts by mass or more and 3000 parts by mass or less, more preferably 400 parts by mass or more and 2500 parts by mass or less, and even more preferably 500 parts by mass or more and 2000 parts by mass or less, relative to 100 parts by mass of the organic phase.
[0074] The method of emulsifying the oily liquid and the aqueous liquid is not particularly limited, but may be a method of emulsifying by starting stirring the oily liquid and the aqueous liquid in a stirring vessel, or a method of adding only the oily liquid in a stirring vessel and starting stirring, and adding the aqueous liquid to the oily liquid in the vessel under stirring using a pump or the like to emulsify. When adding the aqueous liquid to the oily liquid using a pump or the like, the addition rate of the aqueous liquid is not particularly limited, but may be appropriately adjusted within a range of, for example, 10% by mass / min to 1000% by mass / min relative to 100% by mass of the oily liquid. The addition rate of the aqueous liquid is more preferably 100% by mass / min to 800% by mass / min relative to 100% by mass of the oily liquid (organic phase), and even more preferably 200% by mass / min to 600% by mass / min. Furthermore, the specific embodiment of the emulsification step is not particularly limited, and various embodiments can be employed, such as a batch-type emulsification step in which emulsification is performed using a stirring vessel equipped with a stirring device or a centrifugal shaker, and a continuous emulsification step in which an oily liquid and an aqueous liquid are continuously supplied and mixed in a line equipped with a static mixer, a mesh, or the like.
[0075] The stirring speed in the emulsification step is not particularly limited. For example, the stirring power density is 0.01 kW / m 3 More than 10kW / m 3 From the viewpoint of more easily obtaining a HIPE foam having a desired cell structure, the stirring power density in the emulsification step is preferably 0.03 kW / m 3 More than 7kW / m 3 It is more preferable that the stirring power density (unit: kW / m 3 ) is calculated by calculating the power (unit: kW) required for stirring from the torque (unit: N m) and rotation speed (unit: rpm) of the stirring device used in the emulsification process, and multiplying this power by the volume (unit: m 3 ) can be calculated by dividing it by
[0076] The aqueous phase may contain water such as deionized water, a polymerization initiator, an electrolyte, etc. In the emulsification step, for example, an oily liquid and an aqueous liquid are prepared, and the aqueous liquid is added to the oily liquid under stirring to prepare a high internal phase emulsion. In the emulsification step, additives such as a flame retardant, a flame retardant auxiliary, a light resistance agent, and a colorant may be appropriately blended into the aqueous phase and / or the organic phase.
[0077] The flame retardant is used to improve the flame retardancy of the HIPE foam. Examples of the flame retardant include organic compounds containing halogen, phosphorus, nitrogen, silicone, etc.; inorganic compounds containing metal hydroxide, phosphorus, nitrogen, etc. The flame retardant can be used within a range that does not impair the effects of the present invention. When a flame retardant is blended, the blending amount is preferably 5 parts by mass or more and 20 parts by mass or less with respect to 100 parts by mass of the total of the styrene monomer component and the crosslinking agent component constituting the polymer. From the viewpoint of easily imparting excellent flame retardancy even with a small amount of addition, it is preferable to use a brominated bisphenol-based flame retardant having a 2,3-dibromo-2-methylpropyl group and / or a brominated bisphenol-based flame retardant having a 2,3-dibromopropyl group, and it is even more preferable to use 2,2-bis[4-(2,3-dibromo-2-methylpropoxy)-3,5-dibromophenyl]propane.
[0078] In addition, a flame retardant auxiliary can be appropriately blended into the HIPE foam in order to further improve the flame retardancy. For example, when a halogen-based flame retardant is used, if a radical generator such as dicumyl peroxide is used as the flame retardant auxiliary, the decomposition of the radical generator promotes the detachment of halogen from the flame retardant, and the flame retardancy can be improved. When a halogen-based flame retardant is used, if an antimony compound such as antimony trioxide is used as the flame retardant auxiliary, the radical trapping effect of the halogen-based flame retardant and the air blocking effect of antimony oxide act synergistically, and the flame retardancy can be improved. The flame retardant may be used alone, or two or more flame retardants with different flame retardant mechanisms may be used in combination.
[0079] The polymerization initiator is used to initiate the polymerization of the styrene monomer. As the polymerization initiator, a radical polymerization initiator can be used. More specifically, the polymerization initiator includes dilauroyl peroxide (LPO), bis(4-t-butylcyclohexyl) peroxydicarbonate (LTCP), 1,1,3,3-tetramethylbutylperoxy-2-ethylhexanoate, di(3,5,5-trimethylhexanoyl) peroxide, t-butyl peroxy piperate, t-hexyl peroxy piperate, t-butyl peroxy neoheptanoate, t-butyl peroxy neodecanoate, t-hexyl peroxy ne, and the like. Examples of the organic peroxides that can be used include decanoate, di(2-ethylhexyl)peroxydicarbonate, 1,1,3,3-tetramethylbutylperoxyneodecanoate, and benzoyl peroxide; and azo compounds such as 2,2'-azobisisobutyronitrile, 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), 2,2'-azobis(4-dimethylvaleronitrile), dimethyl 2,2'-azobis(2-methylpropionate), and 2,2'-azobis(2-methylbutyronitrile).
[0080] From the viewpoint of suppressing boiling of water during polymerization, the one-hour half-life temperature of the polymerization initiator is preferably 95° C. or lower, and more preferably 90° C. or lower. From the viewpoint of safety, in order to suppress decomposition of the polymerization initiator at room temperature, the one-hour half-life temperature of the polymerization initiator is preferably 50° C. or higher, and more preferably 55° C. or higher.
[0081] As the polymerization initiator, one or more substances can be used. From the viewpoint of shortening the polymerization time without decreasing the uniformity of the apparent density of the HIPE foam, it is preferable to use a combination of an organic peroxide having a one-hour half-life temperature of 50° C. or more and less than 70° C. and an organic peroxide having a one-hour half-life temperature of 70° C. or more and 90° C. or less.
[0082] The polymerization initiator may be added to the organic phase or the aqueous phase. The polymerization initiator may be added to both the organic phase and the aqueous phase. When the polymerization initiator is added to the aqueous phase, a water-soluble polymerization initiator such as 2,2'-azobis[2-(2-imidazolin-2-yl)propane]dihydrochloride, 2,2'-azobis(2-methylpropionamidine)dihydrochloride, potassium persulfate, or ammonium persulfate may be used. The amount of the polymerization initiator to be added may be, for example, within the range of 0.1 parts by mass or more and 5 parts by mass or less with respect to 100 parts by mass of the total of the styrene monomer and the crosslinking agent.
[0083] The emulsifier is used for forming and stabilizing a high internal phase emulsion. For example, a surfactant can be used as the emulsifier. More specifically, the emulsifier may be glycerol esters such as polyglycerol condensed ricinoleate, polyglycerol stearate, polyglycerol oleate, polyglycerol laurate, polyglycerol myristate, etc.; sorbitol esters such as sorbitan oleate, sorbitan stearate, sorbitan laurate, sorbitan laurate, sorbitan palmitate, etc.; ethylene glycol sorbitan esters; ethylene glycol esters; copolymers of polyethylene glycol and polypropylene glycol, etc. These emulsifiers may be used alone, or two or more emulsifiers may be used in combination. The amount of the emulsifier to be added may be, for example, within the range of 1 part by mass to 30 parts by mass relative to 100 parts by mass of the total of the styrene monomer, the crosslinking agent, and the emulsifier.
[0084] The electrolyte is used to impart ionic strength to the aqueous phase and to enhance the stability of the emulsion. As the electrolyte, a water-soluble electrolyte can be used. More specifically, calcium chloride, sodium chloride, magnesium chloride, sodium acetate, sodium citrate, sodium sulfate, calcium sulfate, magnesium sulfate, sodium dihydrogen phosphate, disodium hydrogen phosphate, etc. can be used as the electrolyte. The amount of the electrolyte added may be, for example, within the range of 0.01 parts by mass to 10 parts by mass relative to 100 parts by mass of the aqueous liquid.
[0085] [Polymerization process] In the polymerization step, the water-in-oil type high internal phase emulsion is filled into a reaction vessel, and then a styrene-based monomer is polymerized in the reaction vessel. In the polymerization step, for example, the high internal phase emulsion in the reaction vessel is heated to polymerize the styrene-based monomer to obtain a polymerization product (specifically, a crosslinked polymer containing water). As a method for heating the high internal phase emulsion in the polymerization step, heating with a heat transfer medium liquid such as hot water, heating with electromagnetic waves such as high frequency waves and microwaves, etc. can be suitably adopted.
[0086] The polymerization temperature in the polymerization step is adjusted depending on, for example, the type of styrene-based monomer, the type of polymerization initiator, the type of crosslinking agent, and the like.
[0087] [Drying process] By removing water from the polymerization product obtained as described above, i.e., the crosslinked polymer containing water, a HIPE foam can be obtained (drying step). In the drying step, the polymerization product is dried using an oven, a vacuum dryer, a high-frequency / microwave dryer, or the like. When the drying is completed, the areas where water droplets were present in the emulsion before polymerization become air bubbles in the polymer after drying, and a HIPE foam can be obtained. As an example, a HIPE foam can be obtained by thoroughly drying the polymerization product in an oven set at 90°C until it reaches a constant weight.
[0088] [Dehydration process] In the above-mentioned production method, a dehydration step for removing a part of the water contained in the polymerized product from the polymerized product may be carried out before the drying step, if necessary. By carrying out the dehydration step before the drying step, the time required for the drying step can be further shortened. Examples of a method for removing a part of the water from the polymerized product in the dehydration step include a method of squeezing the polymerized product using a press or a method of centrifuging the polymerized product.
[0089] The dehydration of the polymerization product may be carried out at room temperature (e.g., 23° C.), but it can also be carried out at a temperature equal to or higher than the glass transition temperature of the polymerization product, for example. In this case, dehydration by squeezing or centrifugation becomes easier, and the drying time can be shortened.
[0090] In the dehydration process, it is preferable to maintain the temperature of the polymerization product at or above the glass transition temperature during the period from the start to the completion of the removal of moisture. In this way, by maintaining the temperature of the polymerization product at or above the glass transition temperature during the application of an external force in the dehydration process, the dimensions of the polymerization product are likely to be restored to approximately the dimensions before the dehydration process when the dehydration process is completed and the external force is released. As a result, the structure of the polymerization product before the dehydration process is more likely to be reflected in the HIPE foam after the drying process. Furthermore, in this case, the time required for the drying process can be further shortened. EXAMPLES
[0091] Examples of the vacuum insulation material and the HIPE foam are described below. The styrene monomer, acrylic monomer, crosslinking agent, emulsifier and polymerization initiator used in the examples and comparative examples and their abbreviations are as follows:
[0092] Styrene monomers St: styrene Acrylic monomers BA: Butyl acrylate
[0093] Crosslinking agent DVB: Divinylbenzene (molecular weight 130, "DVB-570" manufactured by Nippon Steel Chemical & Material Co., Ltd., purity 57%) PEGDA: Polyethylene glycol diacrylate (molecular weight 508, "NK Ester A-400" manufactured by Shin-Nakamura Chemical Co., Ltd.)
[0094] Polymerization initiator LPO: Dilauryl peroxide (NOF Corporation "Perloyl (registered trademark) L", 1-hour half-life temperature: 79.5°C) LTCP: Bis(4-t-butylcyclohexyl) peroxydicarbonate (NOF Corporation, "Peroyl TCP", 1-hour half-life temperature: 57.5°C)
[0095] Example 1 In this example, first, a core material made of HIPE foam was produced by the following method.
[0096] [Preparation of core material] First, 82.5 parts by mass of styrene as a styrene-based monomer, 10 parts by mass of divinylbenzene as a crosslinking agent, 7.5 parts by mass of polyglycerin condensed ricinoleate as an emulsifier, 0.5 parts by mass of dilauroyl peroxide and 0.5 parts by mass of bis(4-t-butylcyclohexyl)peroxydicarbonate as polymerization initiators were charged into a 3 L glass vessel equipped with a stirrer with a torque converter. These were mixed in the glass vessel to form an organic phase.
[0097] Next, 0.10 parts by mass of calcium chloride was dissolved as an electrolyte in 1900 parts by mass of deionized water to prepare an aqueous phase. Then, while stirring the organic phase at a rotation speed of 400 rpm, the aqueous phase at a temperature of 20°C was added to the glass container at a rate of about 450 g / min. Stirring was continued for 10 minutes after the addition of the deionized water was completed to prepare a water-in-oil (i.e., W / O) type high internal phase emulsion. The stirring power density after emulsification was completed was 1.4 kW / m 3 The stirring power density (unit: kW / m 3 ) is calculated by calculating the power (unit: kW) from the torque (unit: N m) and rotation speed (unit: rpm) of the agitator, and the volume of the contents (unit: m 3 ) can be calculated by dividing it by
[0098] Next, the stirring power density was set to 0.1 kW / m 3The pressure in the glass container was then lowered to 20°C, and an aspirator was connected to the glass container to reduce the pressure inside the container, thereby removing the microbubbles contained in the emulsion. Ten minutes after the start of the reduction in pressure, the stirring was stopped and the pressure inside the container was returned to atmospheric pressure. The temperature inside the glass container was maintained at 20°C using a chiller from the start to the end of the stirring.
[0099] The high internal phase emulsion thus obtained was filled into a vessel having a length of 200 mm, a width of 200 mm, and a depth of 40 mm. The organic phase of the high internal phase emulsion in the reaction vessel was polymerized in a thermostatic water bath at 70° C. for about 10 hours to form a polymerization product (i.e., a crosslinked polymer containing water) in the reaction vessel. After the polymerization was completed, the reaction vessel was removed from the thermostatic water bath and cooled to room temperature.
[0100] Next, the polymerization product taken out of the reaction vessel was washed with water. After the washing, the polymerization product was dehydrated and then dried in an oven at 90°C until it reached a constant weight, to obtain a HIPE foam. After that, the dried HIPE foam was cut into a plate shape of about 180 mm in length, about 180 mm in width, and about 15 mm in thickness using a band saw, and both sides of the HIPE foam were polished using a drum sander so that the thickness was 10 mm. The HIPE foam thus formed was heated at a temperature of 200°C for 30 minutes to remove volatiles such as moisture contained in the HIPE foam. As a result, a HIPE foam was obtained as the core material of the vacuum insulation material.
[0101] [Preparation of vacuum insulation material] Next, the core material was placed in the outer packaging material, and the inner space of the outer packaging material was evacuated, and then the core material was enclosed in the outer packaging material to produce a vacuum insulation material. To produce the outer packaging material, a multilayer film was used, which had a gas barrier layer made of aluminum foil, a heat-sealed layer made of polyethylene and laminated on one side of the gas barrier layer, and a protective film layer made of a laminated film of a nylon film and a polyethylene terephthalate film and laminated on the back side of the heat-sealed layer in the gas barrier layer. First, two square multilayer films with a length of 230 mm and a width of 230 mm were prepared. Next, the two multilayer films were overlapped so that the heat-sealed layer was on the inside, and three sides of the multilayer film were heat-sealed to obtain a bag-shaped outer packaging material with one side open.
[0102] After the core material was placed in this outer packaging material, the gas present in the inner space of the outer packaging material was exhausted using a vacuum packaging machine (MDJ Co., Ltd. "MDKT500-RD"). Then, after continuing the exhaust for another 60 seconds from the point when the pressure in the inner space reached 1 Pa, the open side of the outer packaging material was heat-sealed to seal the core material in the outer packaging material. Then, the end not including the core material was cut to have dimensions of 200 mm in length, 200 mm in width, and 40 mm in thickness. As a result, the vacuum insulation material of Example 1 was obtained.
[0103] The composition of each component in the HIPE foam of this example is shown in Table 1. The content of each component (styrene monomer and crosslinking agent) in the HIPE foam can be calculated from the blending amount of each component (for the crosslinking agent, the blending amount excluding impurities) at the time of blending and the total blending amount of the styrene monomer component and the crosslinking agent component (excluding impurities).
[0104] Example 2 In this example, a HIPE foam and a vacuum insulation material were produced in the same manner as in Example 1, except that the blending amount of the water phase was changed as shown in Table 1.
[0105] Example 3 In this example, a HIPE foam and a vacuum insulation material were produced in the same manner as in Example 1, except that the blending amount of the water phase and the stirring power density were changed as shown in Table 1.
[0106] (Examples 4 to 5) In these examples, the HIPE foam and the vacuum insulation material were produced in the same manner as in Example 1, except that the stirring power density was changed as shown in Table 1.
[0107] (Examples 6 to 7) In these examples, the HIPE foam and the vacuum insulation material were produced in the same manner as in Example 1, except that the thickness of the dried HIPE foam was changed when it was cut and polished. The thickness of the HIPE foam in Examples 6 to 7 is specifically as shown in Table 1.
[0108] (Comparative Examples 1 to 2) In these comparative examples, HIPE foams and vacuum insulation materials were produced in the same manner as in Example 1, except that the blending amount of the water phase and the stirring power density were changed as shown in Table 2.
[0109] Comparative Example 3 In this example, a HIPE foam and a vacuum insulation material were produced in the same manner as in Example 1, except that no electrolyte was added to the aqueous phase and the stirring power density was changed as shown in Table 2.
[0110] (Comparative Examples 4 to 5) In these comparative examples, HIPE foam and vacuum insulation material were prepared in the same manner as in Example 1, except that the amounts of styrene-based monomer and emulsifier added in the organic phase and the stirring power density were changed as shown in Table 2.
[0111] Comparative Example 6 In this example, the HIPE foam and vacuum insulation material were prepared in the same manner as in Example 1, except that in addition to the styrene monomer, butyl acrylate was blended as an acrylic monomer in the organic phase, in addition to divinylbenzene, polyethylene glycol diacrylate was blended as a polymerization initiator, the amount of electrolyte in the aqueous phase was changed, and the stirring power density was changed as shown in Table 2.
[0112] Next, the evaluation methods for each of the physical properties shown in Tables 1 and 2 will be described.
[0113] [Apparent density of HIPE foam] Three test pieces measuring 50 mm in length, 50 mm in width, and 25 mm in thickness were cut out from the HIPE foam, excluding the skin surface, i.e., the surface that was in contact with the container during polymerization. The mass (unit: kg) of the test piece was then multiplied by the volume (unit: m 3 ) to obtain the apparent density (unit: kg / m 3 The arithmetic average of these apparent densities was calculated as the apparent density of the HIPE foam (unit: kg / m 3 ) was decided.
[0114] [Glass transition temperature Tg of HIPE foam] The glass transition temperature Tg of the HIPE foam was measured based on JIS K7121:1987. Specifically, first, the HIPE foam was cut to obtain a test piece. Next, the test piece was conditioned based on "(3) Measurement of glass transition temperature after a certain heat treatment" in "3. Conditioning of test piece" in JIS K 7121:1987. Then, the conditioned test piece was subjected to differential scanning calorimetry (DSC) to obtain a DSC curve. The midpoint glass transition temperature in the DSC curve obtained in this way was taken as the glass transition temperature Tg of the HIPE foam.
[0115] [Average bubble diameter of HIPE foam] Using a feather blade, samples for observation were cut out from the center of the short side and thickness direction of the rectangular parallelepiped HIPE foam, and from the center of the thickness direction at both ends of the short side. Then, each sample was observed using a low-vacuum scanning electron microscope ("Miniscope (registered trademark) TM3030Plus" manufactured by Hitachi High-Tech Science Corporation), and enlarged photographs of the cross sections of the samples were taken.
[0116] - Sample pretreatment: The sample was treated to make it conductive using a metal coating device ("MSP-1S" manufactured by Vacuum Device Co., Ltd.) Au-Pd was used as the target electrode. Magnification: 50x Acceleration voltage: 5kV Observation conditions: Surface (low magnification) Observation mode: Secondary electrons (standard)
[0117] Next, the enlarged photograph was analyzed using image processing software (NanoHunter NS2K-Pro, manufactured by NanoSystems Co., Ltd.), and the bubble diameter (circle equivalent diameter) of each bubble present on the enlarged photograph was calculated. The arithmetic mean of these bubble diameters was then taken as the average bubble diameter of the HIPE foam. The detailed analysis procedure and conditions were as follows:
[0118] (1) Monochrome conversion (2) Smoothing filter (3x3, 8 neighborhoods, number of processes = 1) (3) Density unevenness correction (brighter than background, size = 5) (4) NS binarization (darker than background, clarity = 9, sensitivity = 1, noise removal, density range = 0 to 255) (5) Contraction (8 neighbors, number of processes = 1) (6) Image selection based on feature (area) (50~∞μm 2 (Only select 8 neighbors) (7) Dilation without connections to neighbors (8 neighbors, number of processes = 3) (8) Measurement of circle equivalent diameter (calculated from area, 8th neighborhood)
[0119] [Average strut width of HIPE foam] First, the HIPE foam was cut at an arbitrary cross section to expose the cut surface. Next, the cut surface was observed using a scanning electron microscope or the like, and an enlarged photograph of the cut surface was obtained. On this enlarged photograph, 20 struts were randomly selected, and the width of the narrowest part of each strut was measured. The arithmetic mean value of the strut widths obtained in this way was taken as the average strut width.
[0120] [HIPE foam compression properties] A test piece 50 mm long, 50 mm wide, and 25 mm thick was cut out from near the center of the HIPE foam, excluding the skin surface, i.e., the surface that was in contact with the container during polymerization. The test piece was conditioned by leaving it in an environment of 23°C temperature and 50% humidity. The conditioned test piece was then used to measure the compressive stress at 5% strain σ5 and the compressive stress at 50% strain σ of the HIPE foam based on JIS6767:1999. 50 Based on these values, the compressive stress σ of the HIPE foam at 50% strain was calculated. 50 Ratio of compressive stress σ5 at 5% strain to σ5 / σ 50 was calculated.
[0121] The compression test was performed using a bench-top precision universal testing machine (Shimadzu Corporation, "AGS-10kNX") at a compression speed of 10 mm / min.
[0122] [Thermal conductivity of HIPE foam] The core material of the vacuum insulation material obtained by the above-mentioned method was used as a test specimen, and the thermal conductivity of the HIPE foam was measured based on JIS A1412-2:1999. More specifically, the test specimen was attached to a thermal conductivity measuring device ("HC-074 / 200" manufactured by Eiko Seiki Co., Ltd.) so that one of the two faces surrounded by a side with a length of 180 mm and a side with a width of 180 mm was in contact with the high-temperature side of the device and the other face was in contact with the low-temperature side. Then, the temperature of the high-temperature side was set to 33°C, and the temperature of the low-temperature side was set to 13°C. Then, the thermal conductivity was measured after the temperature distribution of the test specimen reached a steady state. The average temperature of the test specimen during the thermal conductivity measurement was 23°C.
[0123] [Molecular weight between crosslink points of HIPE foam, Mc] Dynamic viscoelasticity measurements were performed on the HIPE foam under the following measurement conditions: frequency: 1 Hz, load: 98 mN, deformation mode: compression, and a T-E' curve was obtained. In the obtained T-E' curve, any temperature T (unit: K) within the range of Tg+50°C to Tg+80°C, the storage modulus E' (unit: kPa) at that temperature T, and the apparent density ρ (unit: kg / m 3 ) and the molecular weight Mc between crosslink points of the HIPE foam was calculated based on the following formula (1). Mc = 2(1 + μ)ρRT / E' (I)
[0124] In the above formula (I), μ is the Poisson's ratio and R is the gas constant. The value of the Poisson's ratio μ is specifically set to 0.5, and the value of the gas constant R is specifically set to 8.314 J / (K mol).
[0125] [Manufacturability] When exhausting the gas present in the internal space during the manufacturing process of vacuum insulation material, the time required from the start of exhaust until the pressure reached 1 Pa, and the pressure reached when sealing the outer packaging material were measured and are shown in Tables 1 and 2.
[0126] [Thermal insulation] The thermal insulation properties of vacuum insulation materials were evaluated based on their thermal conductivity. The method for measuring the thermal conductivity of vacuum insulation materials is the same as that for HIPE foam, except that vacuum insulation materials were used instead of the core material made of HIPE foam. In the "Evaluation" column for "Thermal Insulation" in Tables 1 and 2, "Good" is entered when the thermal conductivity of the vacuum insulation material is less than 7.5 mW / (m K), and "Poor" is entered when it is 7.5 mW / (m K) or more.
[0127] [Shape retention] The shape retention of the vacuum insulation material was evaluated based on the shrinkage rate of the core material due to reduced pressure. Specifically, the thickness of the thinnest part of the vacuum insulation material was measured, and the thickness of the outer packaging material was subtracted from the measured thickness to calculate the thickness of the core material in the vacuum insulation material. Next, the amount of shrinkage of the core material due to reduced pressure was calculated by subtracting the thickness of the core material in the vacuum insulation material from the thickness of the core material before being enclosed in the outer packaging material. The value expressed as a percentage of the amount of shrinkage of the core material to the thickness of the core material before being enclosed in the outer packaging material was taken as the shrinkage rate of the core material (unit: %). In the "Evaluation" column of "Shape Retention" in Tables 1 and 2, "Good" was written when the shrinkage rate of the core material was 5% or less, and "Poor" was written when it exceeded 5%.
[0128] [Table 1]
[0129] [Table 2]
[0130] As shown in Table 1, the resin constituting the HIPE foams of Examples 1 to 7 is a crosslinked polymer of a styrene-based monomer. The apparent density, average strut width, and compressive stress at 5% strain σ5 of the HIPE foams of Examples 1 to 7 are all within the above-mentioned specific ranges. Therefore, the vacuum insulation materials of Examples 1 to 7 are easy to manufacture, lightweight, and have good thermal insulation properties.
[0131] On the other hand, as shown in Table 2, the HIPE foam of Comparative Example 1 has an apparent density lower than the specific range, and a compressive stress at 5% strain σ5 lower than the specific range. Therefore, the heat insulation of the vacuum insulation material using the HIPE foam of Comparative Example 1 as a core material is insufficient. In addition, when the internal space was decompressed, the core material was not able to withstand the pressure difference between the inside and outside of the vacuum insulation material, and shrunk significantly.
[0132] The HIPE foam of Comparative Example 2 has an apparent density higher than the specific range. Therefore, the vacuum insulation material using the HIPE foam of Comparative Example 2 as a core material had poor insulation properties. This is thought to be because the apparent density of the HIPE foam as a core material was too high, which reduced the thermal resistance of the HIPE foam.
[0133] The average strut width of the HIPE foams of Comparative Examples 3 and 4 was outside the above-mentioned specific range, and therefore the vacuum insulation materials of these Comparative Examples had poor thermal insulation properties.
[0134] The HIPE foams of Comparative Examples 5 and 6 have a compressive stress σ5 at 5% strain lower than the specific range. Therefore, in the vacuum insulation materials using the HIPE foams of these Comparative Examples as the core material, when the internal space was reduced in pressure, the core material contracted significantly because it could not withstand the pressure difference between the inside and outside of the vacuum insulation material.
[0135] The above describes specific embodiments of the vacuum insulation material and HIPE foam of the present invention based on the examples, but the embodiments of the vacuum insulation material and HIPE foam of the present invention are not limited to the embodiments, and the configuration can be changed as appropriate within the scope that does not depart from the spirit of the present invention. [Explanation of symbols]
[0136] 1. Vacuum insulation material 11 Outer packaging material 12 Core material 2. HIPE Form
Claims
1. A vacuum insulation material having an outer packaging material and a core material enclosed in the outer packaging material, The core material is made of HIPE foam, The HIPE foam is composed of a cross-linked polymer of a styrene-based monomer, The apparent density of the HIPE foam is 25 kg / m 3 More than 90kg / m 3 is as follows: The average strut width of the HIPE foam is 2 μm or more and 10 μm or less; A vacuum insulation material, wherein the HIPE foam has a compressive stress at 5% strain of 105 kPa or more.
2. 2. The vacuum insulation material according to claim 1, wherein the thermal conductivity of the vacuum insulation material is less than 7.5 mW / (m·K).
3. 3. The vacuum insulation material according to claim 1, wherein the HIPE foam has a thickness of 2 mm or more and 30 mm or less.
4. 3. The vacuum insulation material according to claim 1, wherein the HIPE foam has a glass transition temperature of 70°C or higher and 150°C or lower.
5. The molecular weight between crosslinking points of the HIPE foam is 8×10 3 Above 2 x 10 5 The vacuum insulation material according to claim 1 or 2, wherein:
6. A HIPE foam used as a core material in a vacuum insulation material having an outer packaging material and a core material enclosed in the outer packaging material, The HIPE foam is composed of a cross-linked polymer of a styrene-based monomer, The apparent density of the HIPE foam is 25 kg / m 3 More than 90kg / m 3 is as follows: The average strut width of the HIPE foam is 2 μm or more and 10 μm or less; The HIPE foam has a compressive stress at 5% strain of 105 kPa or more.
7. 7. The HIPE foam of claim 6, wherein the thickness of the HIPE foam is 2 mm or more and 30 mm or less.
8. 8. The HIPE foam according to claim 6 or 7, wherein the HIPE foam has a glass transition temperature of 70°C or higher and 150°C or lower.
9. The molecular weight between crosslinking points of the HIPE foam is 8×10 3 Above 2 x 10 5 8. A HIPE foam according to claim 6 or 7, wherein:
Citation Information
Patent Citations
Extruded open-cell microcellular foam and method of making same
JP1999504362A